2020
DOI: 10.1136/bmjdrc-2020-001333
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines in early and mid-pregnancy and subsequent risk of gestational diabetes: a longitudinal study in a multiracial cohort

Abstract: IntroductionSeveral adipokines are implicated in the pathophysiology of gestational diabetes mellitus (GDM), however, longitudinal data in early pregnancy on many adipokines are lacking. We prospectively investigated the association of a panel of adipokines in early and mid-pregnancy with GDM risk.Research design and methodsWithin the National Institute of Child Health and Human Development (NICHD) Fetal Growth Studies-Singletons cohort (n=2802), a panel of 10 adipokines (plasma fatty acid binding protein-4 (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 48 publications
1
52
2
Order By: Relevance
“…That effect occurs especially during the pregnancy when the significant increase in chemerin levels is highly pronounced [ 171 , 176 ]. Surprisingly, there was not any correlation between chemerin levels and fasting glucose, C-peptide, and OGTT test results [ 177 , 178 ]. The analyses of relationships between chemerin, fasting insulin, and HOMA-IR (homeostatic model assessment of insulin resistance) values lead to contradictory results.…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
See 4 more Smart Citations
“…That effect occurs especially during the pregnancy when the significant increase in chemerin levels is highly pronounced [ 171 , 176 ]. Surprisingly, there was not any correlation between chemerin levels and fasting glucose, C-peptide, and OGTT test results [ 177 , 178 ]. The analyses of relationships between chemerin, fasting insulin, and HOMA-IR (homeostatic model assessment of insulin resistance) values lead to contradictory results.…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
“…The analyses of relationships between chemerin, fasting insulin, and HOMA-IR (homeostatic model assessment of insulin resistance) values lead to contradictory results. Whereas some authors did not observe any significant correlations between those parameters [ 177 ], the others found that chemerin values were positively markedly correlated with HOMA-IR or insulin levels [ 172 , 179 , 180 , 181 ]. Chemerin values were also found to be positively correlated with fatty acid-binding protein 4, interleukin-6, and tumor necrosis factor-α [ 182 ].…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
See 3 more Smart Citations